Роман «Quid est Veritas?» Наталени Королевої: образно-символічна структура - Василенко, В. (Слово і Час, 2022)
У статті розглядається роман «Quid est Veritas?» Наталени Королевої як спроба переосмислення християнського міфу в українській лі- тературі ХХ ст. Досліджується літературна генеалогія роману, його образно-симво лічна структура та релігійно-філософський зміст. Зазначається, що у своєму романі письменниця подала інтерпретацію християнського міфу через історії його центральних персонажів: Марії Магдалини, Йосифа Ари ма тейського, Понтія Пілата; центральним образом, нав коло якого структурується вся образно-символічна система роману, є чаша Ґрааля. Наголошується, що основним принципом Королевиної інтерпретації стала апокрифізація тексту — уведення в його образно-символічну, сюжетну структури апокрифічних елементів, які руйнують чи, навпаки, доповнюють традиційне сприйняття канонічного матеріа лу. Стверджується, що «Quid est Veritas?» — багатошаровий, складний за формою роман, у якому письменниця порушила важливі морально-етичні, філософські та релігійні питання свого часу. The paper deals with the novel “Quid est Veritas?” by Natalena Koroleva as an attempt to rethink the Christian myth in the Ukrainian literature of the 20th century. The research covers the literary genealogy of the novel, its figurative and symbolic structure, religious and philosophical content. In the novel, Natalena Koroleva presented her interpretation of the Christian myth through rethinking the history of its central characters: Mary Magdalene, Joseph of Arimathea, and Pontius Pilate. The main principle of the author’s interpretation is the implantation of apocryphal elements into the figurative-symbolic and plot structure of the text. Such features may destroy or, on the contrary, complement the traditional perception of canonic material. Depicting the gospel story, Natalena Koroleva combined a historical approach with a mythological one, a canonical version of events and heroes with apocryphal and folklore representations. Numerous chronicles and documents of Roman times, epics, lyrics, and philosophy of antiquity and the Middle Ages, as well as the author’s research work and her experience of archeological excavations in the Middle East, helped a lot in reproducing the period of the acts of Christ and the birth of Christianity. One of the legends told by the author is a story associated with the Holy Grail, which became a subject of a special cult in the history of Christianity and gave rise to many legendary plots. Natalena Koroleva described the history of the Grail as the cup from which Christ drank during the Last Supper and into which one of his secret disciples, Joseph of Arimathea, collected His blood after the crucifixion, as well as other religious and mystical motives drawn from Persian, Jewish, Celtic, and Gallic legends. In these narratives, she purposely left a reserve of artistic uncertainty, which opened opportunities for interpreting the symbols of the Grail in various ways. “Quid est Veritas?” is a complex and multidimensional novel in which the writer tried to comprehend the period of Christ’s life, presenting all possible forms and methods of its perception, reflecting the mythological and scholarly knowledge. Thus she resolved the issues of concern to her and embodied some moral, ethical, philosophical, and religious ideas and visions.